EFFECT OF TRAINING ON THE SUSTAINABILITY OF MOTORCYCLE TAXI BUSINESSES IN NAIROBI COUNTY - Kimathi Samson Murithi,; Prof Evangeline Gichunge,; Dr. Vivian Cherono, (International Journal of Global Economic Light, 2022)
Motorcycles are a popular mode of transportation in developing countries such as Kenya because they are relatively affordable, convenient for short distances and poor roads, and efficient for navigating heavy traffic in many developing cities. Despite these benefits, motorcycles are involved in a substantial number of road traffic crashes and injuries. Research on the role of training in enhancing the sector in Nairobi County is, however, scanty. The objective of the study was the effect of training on the sustainability of motorcycle taxi businesses in Nairobi County. The study was conducted among motorcycle taxi operators. The descriptive research design was adopted. A sample of 249 motorcycle taxi operators in Nairobi County was selected using a systematic random sampling technique. Data was collected using questionnaires. Before data collection, piloting, instrument reliability, and validity, a pilot study was conducted. Data were computed for descriptive statistics (frequencies, means, and percentages) and inferential statistics such as Pearson correlations and Regression analysis. The findings were presented using tables, graphs, and charts. The findings of the study revealed that training had a significant influence on the sustainability of Motorcycle Taxi Businesses in Nairobi County, Kenya. It was also found, most of the operators are trained in road safety, and they apply the skills during their daily operations to a fair extent. Following this, the study recommended that Training should be provided to motorcycle taxi operators on entrepreneurship skills to operators of motorcycle taxi is highly required. Some motorcycle taxi operators who generate sufficient income should be equipped with relevant knowledge of entrepreneurship. Driving schools in the collaboration with the NTSA need to come up with a friendly payment plan for driving school fees that is affordable. The national government through the relevant authorities such as NTSA should come up with a user-friendly curriculum, especially for the persons who have a lower education background